2016
DOI: 10.1002/bdra.23529
|View full text |Cite
|
Sign up to set email alerts
|

A 2015 global update on folic acid‐preventable spina bifida and anencephaly

Abstract: Knowledge that folic acid prevents spina bifida and anencephaly has existed for 25 years, yet only a small fraction of FAP SBA is being prevented worldwide. Several countries still have 5- to 20-fold epidemics of FAP SBA. Implementation of mandatory fortification with folic acid offers governments a proven and rapid way to prevent FAP SBA-associated disability and mortality, and to help achieve health-related Sustainable Development Goals. Birth Defects Research (Part A) 106:520-529, 2016. © 2016 Wiley Periodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 39 publications
0
84
0
Order By: Relevance
“…Long-term intake of folic acid–fortified foods should complement preconceptional folic acid supplementation. Arth et al reported that mandatory folic acid fortification of wheat and maize flour prevented 13.2% folic acid–preventable NTDs (35,500 of approximately 268,700 global cases) in 58 countries [12]. Seventy-eight countries have fortified flour with folic acid mandatorily, while most countries in Asia, Europe and Africa do not mandate folic acid fortification [13].…”
Section: B-vitamins One-carbon Metabolism and Ntdsmentioning
confidence: 99%
“…Long-term intake of folic acid–fortified foods should complement preconceptional folic acid supplementation. Arth et al reported that mandatory folic acid fortification of wheat and maize flour prevented 13.2% folic acid–preventable NTDs (35,500 of approximately 268,700 global cases) in 58 countries [12]. Seventy-eight countries have fortified flour with folic acid mandatorily, while most countries in Asia, Europe and Africa do not mandate folic acid fortification [13].…”
Section: B-vitamins One-carbon Metabolism and Ntdsmentioning
confidence: 99%
“…Preconceptional supplementation with folate increases maternal folate status and prevents a significant number of births with neural tube defects (NTDs) [1–4], even when women are not folate deficient. Therefore, it is recommended that women planning pregnancy or capable of being pregnant should achieve additional intake of 400 µg/day folic acid through supplements and/or fortified foods at least 1 month before pregnancy [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide we are preventing only about 10% of the neural tube defects that can be avoided by folate 1. The EU and some of the world’s largest countries have not adopted mandatory fortification, the only population strategy definitively shown to reduce the incidence of these devastating birth defects 1.…”
Section: Yes—james L Mills Anne M Molloymentioning
confidence: 99%
“…The EU and some of the world’s largest countries have not adopted mandatory fortification, the only population strategy definitively shown to reduce the incidence of these devastating birth defects 1. Some have argued that fortification will benefit only a small number of children at the expense of an unproved risk to a much larger number of elderly people.…”
Section: Yes—james L Mills Anne M Molloymentioning
confidence: 99%